The Role of Self-Esteem and Body Image as Predictors of Self-Harm Behaviors Among Secondary School Students: A Quantitative Analysis - Hengki Yandri; Dosi Juliawati; Alfaiz Alfaiz; Yuzarion Yuzarion; Rani Mega Putri; Emeliya Hardi (TheraEdu: Journal of Therapy and Educational Psychology, 2026)
Self-harm among adolescents represents a significant mental health concern that requires comprehensive understanding for effective intervention development. This quantitative study examined the relationships between self-esteem, body image, and self-harm tendencies among secondary school students. Using a total sampling methodology, 65 students from State Senior High School 1 Sungai Penuh completed validated questionnaires measuring self-esteem, body image, and self-harm behaviours. Multiple linear regression analysis was conducted to assess the predictive relationships between variables. Results indicated that self-esteem and body image combined explained 44.4% of the variance in self-harm behaviours (R² = 0.444), with both independent variables showing significant collective influence on self-harm tendencies. The remaining 55.6% of variance suggests the involvement of additional psychological, environmental, and contextual factors not captured in this study. These findings underscore the importance of developing comprehensive counseling and mental health interventions that address self-esteem enhancement and body image acceptance as preventive strategies for self-harm among adolescents. Implications for school-based guidance and counseling programs are discussed